EDUCATING THE ASPECTS OF THE METAPHORICAL IMAGE OF A PERSON IN THE RUSSIAN WITH IN LITREATURE - N. Chumakov, Aleksey; V. Mochalin, Anatoly (Gênero & Direito, 2020)
The originality of the author՚s individual metaphor in the Russian prose during the first half of the XX century was researched in the article. The specific of the metaphorical description of the inner world of a person and his social existence were considered in the works of I. A. Bunin, V. V. Nabokov, M. M. Prishvin, I. S. Shmelev.